2013
DOI: 10.1016/j.ehj.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trimetazidine on myocardial salvage index in patients with acute ST segment elevation myocardial infarction undergoing primary PCI

Abstract: Introduction: Acute STEMI is the most serious presentation of CAD. Restoration of the coronary flow facilitates cardiomyocyte salvage and decreases cardiac morbidity and mortality. However, reperfusion may result in paradoxical cardiomyocyte dysfunction, a phenomenon termed reperfusion injury. Trimetazidine is a metabolic anti-ischemic drug which is beneficial in reducing periprocedural myocardial reperfusion injury. The aim of the work is to study the effect of trimetazidine on myocardial salvage index in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…However, the work of Steg et al [23] on acute MI patients who received trimetazidine before PCI showed no significant difference in left ventricular wall motion or enzymatic infarct size at the 14-day follow-up. Moreover, the study of Khaled et al [24] on acute MI patients who received trimetazidine before PCI showed no significant difference in myocardial salvage. Additionally, the prospective study of Kim et al [25] on acute MI patients demonstrated that adjunctive trimetazidine therapy had no significant effects upon echocardiographic infarct size at the 1-month and 6-month follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the work of Steg et al [23] on acute MI patients who received trimetazidine before PCI showed no significant difference in left ventricular wall motion or enzymatic infarct size at the 14-day follow-up. Moreover, the study of Khaled et al [24] on acute MI patients who received trimetazidine before PCI showed no significant difference in myocardial salvage. Additionally, the prospective study of Kim et al [25] on acute MI patients demonstrated that adjunctive trimetazidine therapy had no significant effects upon echocardiographic infarct size at the 1-month and 6-month follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…Pada penelitian ini pasien mendapat trimetazidine sebelum dilakukan IKPP, didapatkan hasil myocardial salvage index yang relatif sama pada masing -masing kelompok trimetazidine vs plasebo 29.71±24.4% vs 21.43±21.5% dengan nilai p yang tidak bermakna, penelitian ini memiliki kekurangan yaitu dilakukan hanya pada satu tempat dan jumlah sampel yang sedikit. 16 Penelitian yang dilakukan Kim dkk, meneliti tentang bagaimana perbedaan klinis pasien yang diberikan trimetazidine selama perawatan dirumah sakit dibandingkan dengan pasien yang tidak mendapat trimetazidine. Kemudian diteliti hasil luaran klinis berupa major adverse cardiac events (MACE), didapatkan risiko relatif MACE lebih rendah pada kelompok yang mendapat trimetazidine dibandingkan yang tidak mendapat terapi (angka kejadian 2.3 vs .9.5% ; hazard ratio 0.24,95 % CI 0.10 -0.56, P = 0.001).…”
Section: Peranan Trimetazidine Dalam Menurunkan Akumulasi Netrofilunclassified